Design, Synthesis and Architectures of Hybrid Nanomaterials for Therapy and Diagnosis Applications - Macchione, Micaela A. (Polymers (Basel), 2018)
Hybrid nanomaterials based on inorganic nanoparticles and polymers are highly interesting structures since they combine synergistically the advantageous physical-chemical properties of both inorganic and polymeric components, providing superior functionality to the final material. These unique properties motivate the intensive study of these materials from a multidisciplinary view with the aim of finding novel applications in technological and biomedical fields. Choosing a specific synthetic methodology that allows for control over the surface composition and its architecture, enables not only the examination of the structure/property relationships, but, more importantly, the design of more efficient nanodevices for therapy and diagnosis in nanomedicine. The current review categorizes hybrid nanomaterials into three types of architectures: core-brush, hybrid nanogels, and core-shell. We focus on the analysis of the synthetic approaches that lead to the formation of each type of architecture. Furthermore, most recent advances in therapy and diagnosis applications and some inherent challenges of these materials are herein reviewed.